2020
DOI: 10.1177/1096250620922206
|View full text |Cite
|
Sign up to set email alerts
|

The More the Merrier: Using Collaborative Transdisciplinary Services to Maximize Inclusion and Child Outcomes

Abstract: A local education agency (LEA) preschool program serving 3-to 5-year-old children is committed to high-quality inclusion for young children with disabilities and their neurotypical peers. The school is investing in using evidence-based practices to support all children in learning and development, building meaningful friendships, and a sense of belonging in the community. Each classroom is staffed with a BA-level lead teacher and BA-level teaching assistant. The related service providers including early childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The significance of this finding necessarily emphasises the importance of multi-agency collaboration in assessment and provision for young children with disabilities; those children who had the additional support of an occupational therapist in the classroom, also have higher quality, more well-defined, 'smarter' and more achievable outcomes than those children who did not have such additional support and whose plans are, therefore, mere education plans, rather than true Education, Health and Care plans. This finding adds to the evidence available that teamwork in early childhood intervention leads to better quality provision (Coufal & Woods, 2018;Rausch, Bold & Strain, 2020). However, it also illustrates that the use of additional resources is not a given in EHC provision in England, and many of these plans do not mention any form of intervention outside the education sector.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The significance of this finding necessarily emphasises the importance of multi-agency collaboration in assessment and provision for young children with disabilities; those children who had the additional support of an occupational therapist in the classroom, also have higher quality, more well-defined, 'smarter' and more achievable outcomes than those children who did not have such additional support and whose plans are, therefore, mere education plans, rather than true Education, Health and Care plans. This finding adds to the evidence available that teamwork in early childhood intervention leads to better quality provision (Coufal & Woods, 2018;Rausch, Bold & Strain, 2020). However, it also illustrates that the use of additional resources is not a given in EHC provision in England, and many of these plans do not mention any form of intervention outside the education sector.…”
Section: Discussionmentioning
confidence: 73%
“…The inclusion of additional human resources as part of provision is associated with higher quality outcomes, thus underlining the well-recognised benefits of multi-agency work (e.g. Coufal & Woods, 2018;Rausch, Bold & Strain, 2020). And lastly, when needs are described in detail, provision actions are more specific.…”
Section: Discussionmentioning
confidence: 99%
“…Responding to the widely agreed upon identification of transdisciplinarity as desirable and necessary, although difficult to attain, Haug (2017) describes an ideal state which, unfortunately, is not realized in practice. Without a transdisciplinary approach (Rausch, Bold and Strain, 2021), it is impossible to institute IE and to successfully promote the collaboration of individual social (Bellamy et al, 2013) and special educators who, working together, might promote inclusivity even more effectively (Weiss, Cook and Eren, 2020). In this respect, it can be said that it is the capacity for the various supporting professions to communicate with each other that builds a transdisciplinary approach (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although STEAM disciplines are still taught separately, the current curriculum in early childhood education in Luxembourg (MENJE, 2020b) requires teachers and educators to work in class with a transdisciplinary approach (Rausch et al, 2021) for STEAM disciplines (Liao, 2016), where arts are integrated in STEM (Lavicza et al, 2018). The integrated approach of STEAM disciplines (Kelley and Knowles, 2016;Haas et al, 2021b) has been shown to support students in applying discipline skills and understanding content more easily than taught separately (Burnard et al, 2018;Lavicza et al, 2020;El Bedewy et al, 2022).…”
Section: Steam Transdisciplinary Approachmentioning
confidence: 99%